RELATIONSHIP BETWEEN MOM'S KNOWLEDGE ABOUT TOILET TRAINING WITH HABIT USING DIAPERS IN TODDLER AGE CHILDREN - Tri Marini Supriarti Ningsih (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
HUBUNGAN PENGETAHUAN IBU TENTANG TOILET TRAINING DENGAN KEBIASAAN PEMAKAIAN DIAPERS PADA ANAK USIA TODDLER Tri Marini Supriarti Ningsih Politeknik Kesehatan Kemenkes Medan trimarinisupriartiningsih@gmail.com Abstract Children who wear diapers will experience some barriers in terms of causation which one of them is toilet training. Through toilet training the child will learn how they control the urge to urinate and then they become accustomed to using the toilet independently. The purpose of this study was to determine the relationship between maternal knowledge about toilet training and diapers usage habits at toddler age children in Golden Star PAUD, Beringin District, Deli Serdang District in 2018. This research method was analytical with Cross Sectional research design . Population and sample in this research are all mothers with toddler age children in PAUD Bintang Emas Kecamatan Beringin Deli Serdang Regency. Data were collected using questionnaires with chi square test analysis . Results mothers' knowledge of early childhood toilet training in the Gold Star Beringin Subdistrict of Deli Serdang mostly good (75.6%). The frequency of diapers usage is mostly not used (87.8%). Chi square test results obtained p value 0,000 <0,005. Conclusion There is a significant relationship between maternal knowledge about toilet training and diapers usage habits at toddler age children in Bintang Emas PAUD Beringin District Deli Serdang District. Key : Knowledge, Toilet Training, Diapers, Toddler. Abstrak Anak usia toddler di Indonesia yaitu sekitar 17.091.762 jiwa dari 87,9 juta anak. Menurut Survei Kesehatan Rumah Tangga (SKRT) tahun 2014, diperkirakan jumlah balita yang masih susah mengontrol BAB dan BAK (mengompol) sampai usia prasekolah mencapai 75 juta anak. Tujuan Penelitian untuk mengetahui hubungan pengetahuan ibu tentang toilet training dengan kebiasaan pemakaian diapers pada anak usia toddler di PAUD Bintang Emas Kecamatan Beringin Kabupaten Deli Serdang Tahun 2018. Jenis Penelitian bersifat Analitik dengan desain Cross Sectional. Dimana sampel dalam penelitian ini berjumlah 41 orang. Pengumpulan data menggunakan kuesioner dengan analisis uji chi square. Hasil Penelitian pengetahuan ibu tentang toilet training mayoritas berpengetahuan baik (75,6%). Frekuensi pemakaian diapers kategori tidak pakai (12,2%). Hasil uji chi square diperoleh nilai p 0,000 < 0,05. Kesimpulan adanya hubungan yang signifikan antara pengetahuan ibu tentang toilet training dengan kebiasaan pemakaian diapers pada anak usia toddler. Saran bagi Kepala Sekolah meningkatkan pengetahuan ibu dengan melakukan seminar tentang toilet training dalam pengupayaan pengoptimalan tumbuh kembang anak. Kata kunci : Pengetahuan, Toilet Training, Diapers, Toddler.